Cyclopropane Pipecolic Acids as Templates for Linear and Cyclic Peptidomimetics: Application in the Synthesis of an Arg‐Gly‐Asp (RGD)‐Containing Peptide as an αvβ3 Integrin Ligand. Issue 35 (28th July 2014) - Sernissi, Lorenzo; Petrović, Martina; Scarpi, Dina; Guarna, Antonio; Trabocchi, Andrea; Bianchini, Francesca; Occhiato, Ernesto G.
Abstract The synthesis and evaluation of substituted cyclopropane pipecolic acids (CPA) as conformationally restricted templates for linear and cyclic peptidomimetics is reported. A variety of differently substituted (poly)hydroxy‐ and amino‐2‐azabicyclo[4.1.0]heptane‐1‐carboxylic acids were prepared by means of the Pd‐catalyzed methoxycarbonylation of suitably functionalized lactam‐derived enol phosphates, followed by OH‐directed cyclopropanation. CPAs were successfully introduced into a linear peptide sequence to assess the cis/trans isomerism about the pipecolic acid peptide bond, and in a cyclic peptidomimetic that bore the Arg‐Gly‐Asp (RGD) sequence, which displayed nanomolar activity as antagonist of the αvβ3 integrin in M21 human melanoma cells. Thus, CPAs appear to be suitable for the generation of novel peptidomimetics for drug discovery.